2002
DOI: 10.1021/es010336o
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Transformation of Aquatic Humic Substances by Autochthonous Microorganisms

Abstract: Aquatic humic substances (HS) from a bog lake water, a riverwater, and a groundwater were isolated after enrichment on XAD 8 columns and added to a Czapek-Dox nutrient broth which was used either in full strength or without glucose and/or NaNO3. The individual flasks were inoculated with natural microbial populations of corresponding water samples or with a Pseudomonas fluorescens strain isolated from groundwater. The presence of HS resulted in an increase of bacterial numbers in nearly all cultures incubated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
5

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 38 publications
4
62
0
5
Order By: Relevance
“…Mass balances computed from hydrogeological data showed mineralization of 50-60% of FAs in the deeper part of the shallow aquifer (Heinrichs, 1987). These data suggest that FAs contribute with increasing proportions to the deeper groundwater DOC whereas HAs, with a structure more closely related to biomolecules, probably degrade at a higher rate (Hertkorn et al, 2002a). Alternative mechanisms of removal such as sorption to the mineral soil (Feng et al, 2005) and coagulation by metal ions such as Ca 2+ ,Fe 3+ and Al 3+ (Christl and Kretzschmar, 2007) operate more effectively for HAs than FAs.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Mass balances computed from hydrogeological data showed mineralization of 50-60% of FAs in the deeper part of the shallow aquifer (Heinrichs, 1987). These data suggest that FAs contribute with increasing proportions to the deeper groundwater DOC whereas HAs, with a structure more closely related to biomolecules, probably degrade at a higher rate (Hertkorn et al, 2002a). Alternative mechanisms of removal such as sorption to the mineral soil (Feng et al, 2005) and coagulation by metal ions such as Ca 2+ ,Fe 3+ and Al 3+ (Christl and Kretzschmar, 2007) operate more effectively for HAs than FAs.…”
Section: Resultsmentioning
confidence: 89%
“…Microbial utilization and transformation of humic substances (HS) as confirmed by laboratory studies and observed in surface waters and marine environments (Bianchi et al, 1996;Krumholz et al, 1997;Lovley et al, 1999;Ogawa et al, 1999;Hertkorn et al, 2002a;Hansell et al, 2004;Qualls, 2004;Koch et al, 2005) may also occur in groundwater systems, in which microorganisms use ancient organic material trapped within shales as electron donors (Krumholz et al, 1997). In contrast to other aquatic environments, hitherto few studies have addressed molecular characterization and turnover dynamics of groundwater HS on the basis of natural samples (Leenheer et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…The interest in studying HS from shallow to deep aquifers has increased recently Buckau et al, 2000;Hertkorn et al, 2002;McIntyre et al, 2005;Einsiedl et al, 2008). Most geochemical studies of thermal waters are focused on isotope composition of the water as well as major and minor dissolved ions or trace elements (Varsányi et al, 1997;Kralj, 2004;Yalcin, 2007;Parello et al, 2008;Fekete et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…An increased level of humic substances increases bacterial abundance in humic lakes (Vrede et al, 2003). Autochthonous bacteria utilise and transform aquatic humic substances (HS), decreasing particle size and aromaticity, aliphatic carbon in HS, and increasing the nitrogen content of HS, probably due to some constituents of microbial biomass, such as proteins and amino sugars (Hertkorn et al, 2002). Reduced humic substances (HS) can be reoxidised by anaerobic bacteria, and in general microbial oxidation of HS is a ubiquitous metabolism in the environment (Coates et al, 2002).…”
Section: Discussionmentioning
confidence: 99%